Estimation of accuracy of optimal processing of measurements of multi-position range measuring systems - Васильєв, В. М.; Науменко, К. В. (Problems of Informatization and Control, 2011)
The task of navigation and piloting accuracy improvement through the application of methods that increase the accuracy of determining parameters of the aircraft flight paths of upon the measurements results in the multi-position radio navigation systems has been considered herein. This problem can be solved using the methods of optimal nonlinear filtering is given by the solution of the problem. The results of computer simulation and the comparative evaluation of accuracy are given